[PP.27.15] PREVALENCE OF HYPERTENSION DETERMINED IN COMMUNAL PHARMACIES OF THE VALENCIAN COMMUNITY (RIVALFAR-STUDY). (September 2016) - Giner, V.; Alcázar, S.; Baixauli, V.; Cano, M.; Ferrer, E.; García, M.E.; Prats, R.M.; Sala, E. Rodilla
Abstract : Objective: Hypertension represents an underdiagnosed disease, its real prevalence is difficult to determine in population-based inquiries but also in observational studies. This study aims to measure the prevalence of HTN, associated risk factors and associated clinical diseases in a sanitary environment like communal pharmacies. Design and method: Cross-sectional, observational, descriptive, non-interventional study in 32 communal pharmacies of the Valencian Community, belonging to SEFAC (Spanish Society of Communal Pharmacies), between November 2015 and April 2016. BP variables were measured with a validated device (MOBIL-O-GRAPH, IEM®), according to ESH-recommendations, followed by a 10 items-containing questionnaire and measurement of the waist circumference. Results: During the first month, 638 consecutive patients were recruited. Mean age was 56, 5 ± 14, 1 years, the percentage of men was 38, 6 %, with a global BMI of 28, 5 kg/m2. We found significant differences between women and men in systolic BP (126 vs. 129, p = 0.019), diastolic BP (78 vs. 83, p < 0.001) and waist circumference (88 vs.100, p < 0.001). Prevalence of HTN (35, 5 vs. 47, 0 %; OR = 1, 6; IC: 1, 12–2, 30, p < 0.009) was lower in women, but not obesity (41, 9 vs. 49, 1 %; OR = 0, 75; IC: 0, 54–1, 04, p = 0, 08) or smoking (14, 8 % vs. 19, 9 %; OR = 1, 4; IC: 0, 94–2, 18, p = 0, 09). Visits directly related to BP made up to 35, 4 % of the total count. 28, 7 % of the participants stood under antihypertensive and 26, 8 % under lipid-lowering treatment, 7, 7 % of patients were known diabetics. The prevalence of diagnosed ischemic heart disease was 6, 0 %, that of stroke 4, 2 %. Only 45, 7 % of participants considered their BP was adequately controlled. Noteworthy, under participants without known HTN, prevalence of elevated BP was 25, 3 %, whereas among already treated patients we found increased values in 29, 2 %. Conclusions: This pioneering large scale study involving communal pharmacies shows their capability to determine adequately BP, risk factors and associated clinical diseases, identifying a significant percentage of uncontrolled, already treated patients, as well as a group of de novo, naïve participants with elevated BP. Future studies shall clear if a pharmacy-based strategy is able to improve adherence and control of HTN on the long run.